Origin of Alliance Portfolios: Entrepreneurs, Network Strategies, and Firm Performance - Ozcan, Pinar; Eisenhardt, Kathleen M. (Academy of Management Journal, 2009)
Alliance portfolios are ubiquitous and influential for firm performance. Extant research addresses attributes of high-performing alliance portfolios but not how executives originate such portfolios. In our inductive case study of six entrepreneurial rivals in the wireless gaming industry, we find that executives are more likely to originate high-performing portfolios when they visualize their portfolios in the context of the entire industry as opposed to a series of single ties and when they simultaneously form ties with multiple partners. The emergent theoretical framework emphasizes agency and strategic action in contrast to a deterministic account of dyadic interdependence and social embeddedness.